Analysis of basic hospital pricing using the unit cost double distribution method - Nurmansyah Agung; Kristianto Giovanny Bangun; Santoso Cahyo Budi; Saraswati Esti; Anggraeniko Litya Surisdani (BIO Web of Conferences)
The basic rate of a hospital is a benchmark for the sustainability of a hospital in providing services to hospital patients. Determining rates in a hospital requires a lot of consideration, many factors that become variables to be taken into account. This study aims to determine a method of determining rates that are in accordance with the needs of the hospital. This study is a descriptive study of the assessment of previous studies compared to the double distribution method. Most studies state that the ABC method is appropriate for determining hospital rates because it calculates rates based on activities in the hospital. However, with the double distribution method, it applies two stages to determine prices from work units that do not have income to the second stage, namely service units. So that the cost burden will end up in the service unit. Basically, the determination of the calculation method needs to be adjusted to the complexity of the hospital itself, because the application of costs in each has differences from one another.